Antimicrobial activity of Ruta angustifolia L. Pers against periodontal pathogen: Porphyromonas gingivalis - Husna Hazirah Bakri; Syarifah Nur Syed Abdul Rahman; Zarith Safinaz Dol Bakri; Elly Munadziroh; Wan Himratul Aznita Wan Harun (PeerJ)
Background Porphyromonas gingivalis is widely recognised as a periodontal pathogen. In recent years, there has been growing interest in the use of medicinal plant extracts as alternative treatments for periodontitis to combat the emergence of antibiotic-resistant bacteria. Ruta angustifolia L. Pers has been traditionally used to treat various ailments, including oral bacterial infections. However, the antimicrobial potential of R. angustifolia extracts against the periodontal pathogen P. gingivalis remains unexplored. Hence, the aim of this study was to investigate the antimicrobial activity of R. angustifolia extracts against P. gingivalis. Methods The antimicrobial activity of R. angustifolia extracts (crude methanol, hexane and chloroform fractionated extracts) against P. gingivalis was evaluated using the well diffusion method. Additionally, the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined. Biofilm biomass assessment and live/dead cell viability assays were performed to analyse the effect of R. angustifolia extracts. Ultrastructural morphological changes in P. gingivalis cells were determined using field emission scanning electron microscopy (FE-SEM). Results It was found that P. gingivalis was susceptible to R. angustifolia extracts, with the chloroform fractionated extract exhibiting the highest inhibition zones. The MIC and MBC of chloroform fractionated extract were determined to be 6.25 mg/mL which substantially reduced P. gingivalis biofilm biomass. Live/dead cell viability assays showed the highest percentage of dead P. gingivalis cells after 48 h of incubation. FE-SEM confirmed that the chloroform fractionated extract effectively damaged the bacterial cell wall and altered the ultrastructural morphology of P. gingivalis. Conclusion The results indicated that extracts of R. angustifolia has the potential to be used as an alternative treatment in addition to conventional periodontal therapies.